En FFAR(a) för konkurrensen? - En konkurrensrättslig analys av avgiftstaket i artikel 15(2) FFAR - Jansson,Albin (2024)
This thesis examines the fee cap for the remuneration of football agents introduced under article 15(2) of the FIFA Football Agents Regulations and its compliance with EU competition law, particularly article 101 TFEU. The fee cap seeks to promote transparency, economic fairness, and the protection of young players in the football transfer market. The analysis also considers the legal specificity of sports, a concept recognized in article 165 TFEU and the case law of the Court of Justice of the European Union (CJEU). This specificity allows certain sports-related rules and values, such as protecting the integrity of sports and maintaining competitive balance to justify some restrictions of competition. The thesis explores whether the regulation constitutes a restriction of competition and whether it can be justified under the exemption in article 101(3) TFEU or the Wouters and Meca-Medina case law. The conclusion suggests that Article 15(2) may represent a restriction of competition. At the same time FIFA can argue for its legitimacy and proportionality based on the unique characteristics of sports. The legal assessment of the regulation’s compatibility with EU law is complex and depends on how its purpose and necessity are evaluated in the ongoing preliminary ruling before the CJEU.
Keywords: EU-rätt; konkurrensrätt; FIFA